Effects of Irradiance and Temperature on the Photosynthesis of the Crustose Coralline Algae Pneophyllum fragile (Corallinales, Rhodophyta) in the Coastal Waters of Korea - Ju-Wook Baek; Jae Seong Lee; Sung-Han Kim; Taehee Lee; Seung Won Jung; Won-Chan Lee; Kyung-Tae Kim; Sung-Uk An (Journal of Marine Science and Engineering, 2022)
We investigated the photosynthetic characteristics of the crustose coralline alga Pneophyllum fragile (Corallinales, Rhodophyta) according to elevated water temperature and irradiance on the coast of Jeju in 2018. P. fragile was cultured under different temperature (11 °C, 21 °C, 26 °C, and 31 °C) and irradiance (0–1250 μmol photon m−2 s−1) conditions. Oxygen (O2) concentrations at the P. fragile mat–water interface (MWI) were measured using an O2 microsensor. At the MWI, the diffusive boundary layer thicknesses ranged from 200 to 400 μm. The O2 concentrations at the mat surface increased in response to increasing irradiance, and reached 344% air saturation. The maximum photosynthesis capacity (Pmax) and respiration rate in the dark (Rd) at 31 °C were about 3 times higher than those recorded at 11 °C. The compensation irradiance (Ec) and saturation irradiance (Ek) increased with increasing water temperature. The Pmax, Rd, and Ec were statistically correlated with temperature (p < 0.05). The Ek increased up to 833 μmol photon m−2 s−1 at 31 °C and exhibited a strong dependence on irradiance at high temperatures. The adaptability of P. fragile to high temperatures and strong irradiance was distinct from that observed for coralline algae in other temperate waters.